Management Of Class II Malocclusion – Orthodontic Camouflage Treatment: Case Report - Raluca Maria Mocanu (Romanian Journal of Oral Rehabilitation, 2013)
In Class II malocclusion, a variety of treatment modalities have been presented in the literature. The camouflage orthodontic is a treatment alternative, involving extraction of premolars. In the absence of an important mandibular crowding, the interdental relations can be obtained by numerical reduction in the upper arch, resulting in a Class II molar and a Class I canine relationship. It is important to choose ideal maxillary incisor position over Class I posterior occlusion. This case report presents one such case of a 15 year old female, having a skeletal Class II malocclusion with labial ectopic upper canines. The selective extraction of maxillary first premolar was considered an acceptable compromised. Following treatment, great improvement in the aspect of profile and smile were achieved and there was an increase in the patient’s confidence and quality of life.